2021
DOI: 10.1186/s13000-021-01093-4
|View full text |Cite
|
Sign up to set email alerts
|

Significance of mesothelin and CA125 expression in endometrial carcinoma: a retrospective analysis

Abstract: Background This study aimed to investigate the association between clinicopathologic factors, mesothelin, and cancer antigen (CA) 125 in endometrial carcinoma. Methods Between 1989 and 2017, patients with endometrial carcinoma who underwent total hysterectomy and bilateral salpingo-oophorectomy at our hospital were identified. The association between either or both immunochemical expression of mesothelin and CA125 and clinicopathological features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In clinical practice, CA125 has been routinely used to diagnose a variety of malignancies, especially epithelial ovarian cancer [ 28 ]. Quan et al [ 29 ] demonstrated that serum CA125 significantly correlated with clinicopathological risk factors, such as depth of myometrial invasion, LN status, and FIGO stage and that CA125 is a promising prognostic indicator for EC [ 30 , 31 ]. In our study, CA125 could be used as an independent predictor of PLNM in EC patients, which is consistent with the results of Lei et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, CA125 has been routinely used to diagnose a variety of malignancies, especially epithelial ovarian cancer [ 28 ]. Quan et al [ 29 ] demonstrated that serum CA125 significantly correlated with clinicopathological risk factors, such as depth of myometrial invasion, LN status, and FIGO stage and that CA125 is a promising prognostic indicator for EC [ 30 , 31 ]. In our study, CA125 could be used as an independent predictor of PLNM in EC patients, which is consistent with the results of Lei et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSLN-positive cancers are well known to co-express immunosuppressive HIO factors. Cancers expressing high MSLN levels such as malignant pleural mesothelioma, nonmucinous ovarian, endometrial, and pancreatic adenocarcinoma have all been documented to express the immunosuppressive MUC16/CA125 [26][27][28] as well as MUC1 [29][30][31][32]. Antibody-based therapies that employ ADCC and CDC immune effector activities have had modest efficacy in treating these diseases and only few studies have correlated HIO factor levels with preclinical or clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that serum CA125 is a predictor of prognosis in various malignancies, including epithelial ovarian cancer, [7] cervical adenocarcinoma, [9] and endometrial carcinoma. [13] CA125 is a transmembrane mucin encoded by the mucin 16 (MUC16) gene. [14] CA125/MUC16 might also play an important role in the tumorigenesis and metastasis of pancreatic cancer [15] and ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%